1976
DOI: 10.1901/jeab.1976.26-289
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF REARING ENVIRONMENTS ON THE CONTRAFREELOADING PHENOMENON IN RATS1

Abstract: Eight naive rats were reared in enriched or impoverished environments for 39 days after weaning and then lived in operant chambers, in which they could obtain food pellets freely or by lever pressing, for 25 or 30 days. The animals raised in an impoverished environment acquired the bar-press response quickly when placed in the operant chambers and maintained a preference for obtaining food via bar pressing. Animals raised in an enriched environment did not learn to lever press, as demonstrated by low levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
14
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…Similar procedures have generally been employed in subsequent research, but it is not necessary for rats to have experience with response-contingent reinforcement or to be tested in discrete sessions with controlled deprivation in order for them to exhibit contrafreeloading. When naive rats were continuously housed in operant chambers with both free and response-contingent food available on CRF, leverpressing was acquired and maintained for 30 or 100 days (Coburn & Tarte, 1976;Kopp, Bourland, Tarte, & Vernon, 1976).When rats live continuously in experimental chambers with no food other than that produced by responding, their daily response rates increase as the value of a fixed ratio (FR) schedule is increased from CRF to FR240, so that roughly constant food intake is maintained (Collier, Hirsch, & Hamlin, 1972; see also Collier, Johnson, Hill, & Kaufman, 1986). This situation is referred to as a closed economy (see, e.g., Collier, 1983;Hursh, 1984).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar procedures have generally been employed in subsequent research, but it is not necessary for rats to have experience with response-contingent reinforcement or to be tested in discrete sessions with controlled deprivation in order for them to exhibit contrafreeloading. When naive rats were continuously housed in operant chambers with both free and response-contingent food available on CRF, leverpressing was acquired and maintained for 30 or 100 days (Coburn & Tarte, 1976;Kopp, Bourland, Tarte, & Vernon, 1976).When rats live continuously in experimental chambers with no food other than that produced by responding, their daily response rates increase as the value of a fixed ratio (FR) schedule is increased from CRF to FR240, so that roughly constant food intake is maintained (Collier, Hirsch, & Hamlin, 1972; see also Collier, Johnson, Hill, & Kaufman, 1986). This situation is referred to as a closed economy (see, e.g., Collier, 1983;Hursh, 1984).…”
mentioning
confidence: 99%
“…Similar procedures have generally been employed in subsequent research, but it is not necessary for rats to have experience with response-contingent reinforcement or to be tested in discrete sessions with controlled deprivation in order for them to exhibit contrafreeloading. When naive rats were continuously housed in operant chambers with both free and response-contingent food available on CRF, leverpressing was acquired and maintained for 30 or 100 days (Coburn & Tarte, 1976;Kopp, Bourland, Tarte, & Vernon, 1976).…”
mentioning
confidence: 99%
“…In my estimation, the fact that this ever occurs is striking; that it takes only several days to develop is phenomenal. The finding by Coburn and Tarte (1976) that rats reared in enriched environments failed to acquire a barpress response appears attributable to the fact that .these animals only rarely strayed from the free food source (p. 92) and consequently made only infrequent contact with the programmed response-reinforcer contingency.…”
mentioning
confidence: 98%
“…Yet Kopp et al (p. 52) reported that three of their four rats developed consistent barpressing within several days, a time period similar to that necessary for naive pigeons to learn a food-producing response in the presence of free food (Neuringer, 1969). Mcl.aughlin, Kleinman, and Vaughn (1973) reported that naive rats acquired a barpress response within 7 to 10 days, although responding was again maintained at a low rate, and Coburn and Tarte (1976) found that rats reared in impoverished environments began responding for food from the outset of their experiment.…”
mentioning
confidence: 99%
See 1 more Smart Citation